Persepsi Kualitas dan Performa Sistem Aplikasi Akuntansi MYOB pada Pengguna Level Dasar - Septian Bayu Kristanto; Carlin Windyan (STIE Indonesia Banking School, 2017)
The purpose of this study want to examine the effect of System Quality on Service Quality, System Quality to Work Performance, and Service Quality to Work Performance. The object in this research is MYOB accounting software. The data gathered from questionnaires in 2 types, physicals (paper) and online (using Google form). From 315 questionnaires distributed consisted of 194 respondents through online, and 116 respondents through the paper form. All the questionnaires are returned. The obtained data were analyzed using structural equation modeling. The result of data analysis showed that the System Quality has positive significant effect on the Service Quality, Service Quality has positive significant effect on Work Performance, and System Quality has positive significant effect on Work Performance. The overall result indicates that MYOB has a good quality and related to user performance. Specifically, the user refers to the basic user, which is a university student.